Mystery of the Moorish Science Temple: Southern Blacks and American Alternative Spirituality in 1920s Chicago - Nance, Susan (Religion and American culture, 2002)
In 1926, the well-known black scholar Ira De Augustine Reid complained that storefront churches were “a general nuisance. Neither their appearance nor their character warrants the respect of the Community.” Mortified, he described the founders of these informal assemblies: “He conducts his Services on such days as he feels disposed mentally and indisposed financially. To this gentleman of the cloth… the church is a legitimate business.” More to the point, he described his perception of the many southern migrants who aspired to found their own churches and religions, recounting how one “young swain” had announced to the leadership of a large traditional black congregation that he had had a dream. “In this dream a still small voice told him to ‘G. P. C.’ and when he heard it he knew that he was instructed to ‘Go Preach Christ.’ After further questioning by the Council, the chairman told him that he had misinterpreted his dream, for it certainly meant ‘Go plant corn’” For many educated African Americans, the idea of southern migrants presuming to enjoy their own religious traditions on their own terms in the urban North was ludicrous.